Axial Shortening in Myopic Children after Repeated Low-Level Red-Light Therapy: Post Hoc Analysis of a Randomized Trial - Wang, Wei; Jiang, Yu; Zhu, Zhuoting; Zhang, Shiran; Xuan, Meng; Tan, Xingping; Kong, Xiangbin; Zhong, Hui; Bulloch, Gabriella; Xiong, Ruilin; Yuan, Yixiong; Chen, Yanping; et al. (Ophthalmology and therapy, 2023)
Introduction Axial length (AL) elongation in myopia is considered irreversible. We aimed to systemically report unexpected AL shortening observed in a randomized clinical trial (RCT) after repeated low-level red-light (RLRL) therapy. Methods This is a post hoc analysis of a multicenter, single-masked RCT. Two hundred sixty-four myopic children aged 8–13 years allocated to RLRL treatment (intervention group) or a single vision spectacle (SVS, control group) were included. AL was measured using an IOL-master 500 at baseline, 1-, 3-, 6-, and 12-month follow-up visits. AL shortening was defined as AL reduction from baseline to follow-up visits at three cutoffs: > 0.05 mm, > 0.10 mm, and > 0.20 mm. Frequency of AL shortening at different cutoffs was calculated. Analysis was done with intent to treat (ITT). Results At 12-months follow up, frequency of AL shortening > 0.05 mm was 26/119 (21.85%) and 2/145 (1.38%) for the RLRL group versus the control group, respectively. The frequency was 18/119 (15.13%) versus 0/145 (0%) for AL shortening > 0.10 mm, and 7/119 (5.88%) versus 0/145 (0%), for AL shortening > 0.20 mm, respectively ( p < 0.001). Mean AL shortening after 12 months (SD) was −0.156 (0.086) mm in the RLRL group and −0.06 mm in the control group. Age was significantly associated with AL shortening in the multivariable analysis. For the RLRL group that exhibited AL shortening ( n = 56), choroidal thickness (ChT) thickening (0.056 mm) could only explain 28.3% of AL shortening (−0.20 mm). Conclusion Nearly a quarter of children had > 0.05 mm AL shortening following 12 months of RLRL therapy, whereas AL shortening rarely occurred among controls. Trial Registration ClinicalTrials.gov (NCT04073238).